A multi‐century meteo‐hydrological analysis for the Adda river basin (Central Alps). Part I: Gridded monthly precipitation (1800–2016) records. (10th May 2020) - Crespi, Alice; Brunetti, Michele; Ranzi, Roberto; Tomirotti, Massimo; Maugeri, Maurizio
Abstract: The 1800–2016 monthly precipitation record for the upper Adda river basin is presented. It is computed by applying the anomaly method to a quality‐checked and homogenized observation database. The reconstruction accuracy and its evolution over the study period is evaluated at both station and grid‐cell levels. The anomaly‐based interpolation provides rather robust estimates even for the early years of sparse station coverage with basin precipitation reconstruction errors around 10%. The Theil‐Sen trend analysis on the basin precipitation series shows significant (Mann‐Kendall p value <.05) long‐term tendencies of −3.8 ± 1.9% and −9.3 ± 3.8% century −1 for annual and autumn precipitation, respectively, even though the annual trend is not significant by excluding the first decades from the evaluation. As the basin precipitation record is expected to be underestimated due to the rain‐gauge snow undercatch, the monthly precipitation fields are subjected to a correction procedure which allows to derive the multiplicative correcting constant to be applied to the basin annual precipitation series. The comparison between 1845 and 2016 yearly corrected precipitation and runoff records highlights current annual water losses of about 400 mm while the annual runoff coefficients exhibit a long‐term significant decrease of −6.4 ± 1.0% century −1 . This change in the hydrological cycle is mostly to be ascribed to the strong long‐term reduction in annual runoff values (−11.8 ± 3.2% century −1 ) driven by increasing evapotranspiration due to both temperature increase and, likely, land‐use changes. Abstract : The paper presents the 30‐arc sec gridded dataset of 1800–2016 monthly precipitation records for the upper part of Adda river basin (Central Alps) reconstructed by an anomaly‐based method and a dense database of quality‐checked and homogenized observations. The areal basin monthly precipitation record was derived, analysed for variability and trend and compared with the 1845–2016 basin annual runoff series presented in the companion paper. The annual runoff coefficient exhibits a long‐term significant decrease mostly driven by increasing evapotranspiration.